Enhancement of the phase transformation temperature of gamma-Fe2O3 by Zn2+ doping - Deka, Sasanka; Joy, Pattayil Alias (Journal of Materials Chemistry, 2007)
The phase transformation temperature of gamma-Fe2O3 to alpha-Fe2O3 is increased with Zn2+ doping and enhancement of the transition temperature by similar to 100 degrees C is obtained for doping of >= 15 mol% Zn in nanocrystalline gamma-Fe2O3 synthesized by an autocombustion method.